Financial Cycle Intensity In The Indonesian Green Finance - Edwin Basmar; Gunawan Baharuddin (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2025)
The financial cycle intensity as an indicator in identifying, measuring and analyzing the green finance effectiveness in the banking sector. This study uses time series data from Bank Indonesia's Financial Report from 1980 to 2024. In order to measure macroeconomic pressures on the financial cycle intensity that have an impact on the banking sector performance. The data is analyzed with the Ed Waves Index development model using E-views 9 software. The paper's main finding that the financial cycle intensity has a significant effect on the banking intermediary function. However, the banking intermediary function works in an unbalanced condition, resulting in high Non-Performing Loans accompanied by a lack of financial liquidity. Therefore green finance in the banking sector can only increase economic growth and has not been able to maintain financial stability. Furthemore, Bank Indonesia has a strong role in maintaining the financial cycle movement in order to improve the banking intermediary function towards the green finance effectiveness in achieving a balance between the financial ecosystem and the environmental ecosystem simultaneously.